Do birth outcomes mediate the association between drug use in pregnancy and neonatal metabolic bone disease? A prospective cohort study of 10,801 Chinese women - Jiang, Honglin; Guo, Jialin; Li, Jing; Li, Chunlin; Du, Wenchong; Canavese, Federico; Xie, Feng; Li, Huajing; Yang, Jian; Ying, Hao; Hua, Jing (Frontiers in Public Health, 2024)
Background Prenatal drug use may cause toxicity to bone health in newborns. We aimed to examine whether birth outcomes mediate the association between medication use and neonatal metabolic bone disease (MBD). Methods A prospective cohort of 10,801 pregnant women (17–49 years) and their infants followed at a single center from 1 January 2012 to 31 December 2021 were included. Based on four single drugs, comprehensive medication use was determined and categorized into three groups using latent-class analysis: group 1 included antibiotics and furosemide or less than two drugs except for MgSO4; group 2 included MgSO4 without antibiotics or furosemide; and group 3 encompassed dexamethasone and antibiotics. Mediation analysis was conducted to assess the mediating effects of prematurity, low birth weight (LBW), and small for gestational age (SGA). Results There were 138 (1.3%) infants with MBD; 2,701 (25%) were born preterm, 1717 (15.9%) had LBW, and 303 (2.8%) were SGA. Pregnant women in groups 2 and 3 were 2.52 to 14.66 times more likely to deliver an infant with MBD than those in group 1. Only LBW showed a significant mediating effect on the association between comprehensive medication use and MBD, with a mediation proportion of 51.8% (45.0–64.1%, p < 0.001). Conclusion Comprehensive medication use during pregnancy was associated with an increased risk of neonatal MBD, largely mediated by LBW. Early antepartum monitoring and prevention targeting adverse birth outcomes are necessary to mitigate the risk of MBD.